Sexual dysfunction in Brazilian patients with multiple sclerosis - Elisa Matias Vieira de Melo; Vinicius Andreoli Schoeps; Flavia Fairbanks Lima de Oliveira; Maria Fernanda Mendes; Guilherme Sciascia do Olival (Arquivos de Neuro-Psiquiatria, 2023)
Background People with multiple sclerosis (PwMS) show an increased risk of sexual dysfunction (SD), both in women and men. Objective The aim of the present study was to apply the Multiple Sclerosis Intimacy and Sexuality Questionnaire-19 (MSISQ-19) and evaluate our results by comparing them with those in in the literature, as well as to assess the ease of applying the scale and the engagement of the patients in discussing the topic of sexuality. Methods We developed and applied a web-based Google form questionnaire that the respondents completed online, which included the MSISQ-19, for the assessment of sexual function. Baseline characteristics were reported as proportions and mean ± standard deviation (SD) or median ± interquartile range (IQR) as appropriate according to data distribution. Categorical variables were stratified by sex and compared with chi-squared tests. Statistical analyses were performed using STATA v. 16 (StataCorp., College Station, TX, USA). Results Of the 621 respondents, 541 were included in the analysis. Among the patients with MS, a total of 347 (64.14%) exhibited SD. When stratified by gender, the frequencies of SD were not significantly different. Conclusion There is a high incidence of sexual dysfunction among PwMS and we need to identify the reasons for this and implement strategies to treat and counsel our patients. The MSISQ-19 can be used to help clinicians to assess sexual functioning in a quick and easy way and give patients the possibility to address this topic and receive appropriate help and support.